Is It Appropriate to Treat Sarcoma Metastases With Intramedullary Nailing?. Issue 1 (January 2017) - Moon, Bryan S.; Dunbar, Dwayne J.; Lin, Patrick P.; Satcher, Robert L.; Bird, Justin E.; Lewis, Valerae O.
Abstract: Background: Patients with primary bone and soft tissue sarcoma are at risk for skeletal metastases. Although uncommon, these metastases can result in impending or pathologic fractures. Intramedullary nailing traditionally has been an accepted form of palliative treatment for patients with metastatic carcinoma, but we could find no studies that report specifically on intramedullary nailing of metastatic sarcoma lesions. Questions/purposes: We asked: (1) What is the survival of patients with an impending or pathologic fracture from a sarcoma metastasis? (2) What proportion of patients treated with intramedullary nailing subsequently underwent a revision procedure or nail removal during their lifetimes? Methods: Between 1996 and 2014, we performed 40 intramedullary nailing procedures in 34 patients with multifocal metastases from sarcomas who showed signs or symptoms of impending fracture or who presented with a pathologic fracture. All of these patients are accounted for, either through the time of death or to the present, and all are included at a mean of 13 months (range, 0.3‐86 months) in this retrospective study. During the study period, we generally applied the same surgical indications for patients with nailing of metastatic sarcoma lesions as we did for patients with metastatic carcinoma; in general, we used intramedullary nailing (with or without cement) rather than resection for diaphyseal lesions with less cortical destruction and no substantial soft tissue mass or metadiaphyseal lesions that could be adequately supplemented with cementation. The goal was to use this approach when it would allow immediate weightbearing, or in patients whose medical conditions were such that a more‐extensive procedure seemed unsafe. During the same period, an additional 58 patients underwent resection procedures for metastatic sarcomas to long bones because they either did not meet the above indications, had a solitary resectable metastasis, or because of surgeon preference; these patients were excluded from this study. The median age of the patients was 52 years (range, 27‐81 years). Eleven patients with 11 impending or pathologic fractures were documented to have received either preoperative or postoperative radiation therapy and 29 patients received some form of chemotherapy. Results: Thirty (88%) patients died during the period of observation, at a median of 5 months (range, 0.3‐80 months) after surgery. Twenty‐nine patients (85%) underwent no additional surgery and retained their original intramedullary nail. One patient (3%) underwent nail removal for infection, and four patients (12%) underwent further surgical revision secondary to local progression. Conclusions: Patients with an impending or pathologic fracture from multifocal metastatic sarcoma to a long bone have a dismal prognosis, but they may gain short‐term benefit from surgical fixation with the goal of reducing pain and maintaining mobility. Although we have no group for comparison, such as treating with radiotherapy alone or resection and an endoprosthesis, our findings suggest that use of intramedullary nails is helpful for providing fixation that in most instances lasts for the lifetime of patients with multifocal bone metastases from sarcomas. Level of Evidence: Level IV, therapeutic study.